Reconstruction of metabolic brain model with the aid of physiologically based pharmacokinetic modelling in the presence of autism spectrum disorder - Erimli, Sena. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder with only symptomatic medical treatment with increasing prevalence. This study aims to reconstruct a genome-scale metabolic brain model that is expanded via genes and reactions related to ASD and observe changes in dopamine D2 receptors in the presence of antipsychotics. For this aim, iMS570, iNL403, and MODEL1608180000 are merged. After standardization, duplicate reaction removals, deletion of zero flux reactions, and expanding model with ASD related genes and reactions, the final model consists of 1638 reactions, 1358 metabolites, and 756 genes. For further investigations of the autism-specific brain model, transcriptome gene expression data GSE28475 is prepared and integrated. Autism-specific brain model shows mitochondrial and glutaminergic dysfunctions. Final 18360 unique genes are assigned as up-or down-regulated based on threshold determined by downregulated SHANK3 expression and 30% of averages of gene expression data. Additionally, the physiology-based pharmacokinetic (PBPK) model of risperidone and its metabolite paliperidone is simulated. Both drugs are antipsychotics that are used in ASD symptoms. First, simulations are performed to observe population density, CYP2D6 subtypes, ethnicity, total hepatic clearance, and P-gp concentration changes for 2 mg risperidone. PBPK simulation results of experimental articles were in the range of literature findings. Receptor occupancy simulations with chronic dosing underestimate plasma concentrations, but results are still in the range. With down-regulation of the SLC6A3 dopamine transporter gene, which is used to mimic DRD2 gene, proportional to receptor occupancy findings, the effect of risperidone on autism-specific brain model is investigated. Glutaminergic neurotransmission is decreased below healthy brain level, and mitochondrial dysfunction was relieved but still not in the healthy range. Reconstruction of ASD-specific brain model with PBPK modeling enhancement is promising work to better under disease mechanism.
Keywords: Autism spectrum disorders.